Multi-method groundwater recharge estimation at Eshito micro-watershed, Rift Valley Basin in Ethiopia - Ferede, M.; Haile, Alemseged Tamiru; Walker, D.; Gowing, J.; Parkin, G. (Informa UK Limited, 2020)
Understanding recharge processes is fundamental to improve sustainable groundwater resource management. Shallow groundwater (SGW) is being developed for multiple purposes in Ethiopia without consideration of monitoring. We established a citizen science-based hydro-meteorological monitoring network, with a focus on SGW recharge estimation, in Eshito micro-watershed, Ethiopia. Citizen scientists collected rainfall, groundwater-level and stream water-level data. We characterized the shallow aquifer using pumping tests. The data were used to estimate SGW recharge using three methods: chloride mass balance, water-level fluctuation (WLF) and baseflow separation. Approximately 20% and 35% of annual rainfall amount contributes to recharge based on the chloride mass balance and WLF results, respectively. Baseflow separation showed recharge values for the watershed vary from 38% to 28% of annual rainfall at the upstream and downstream gauging stations, respectively. This study shows that the recharge in previously unmonitored micro-watersheds can be studied if citizens are involved in data generation.